Digestible lysine for broiler chickens with lower genetic potential grown on free-range system - Eduardo Souza do Nascimento; Cristina Amorim Ribeiro de Lima; Ronner Joaquim Mendonça Brasil; Noédson de Jesus Beltrão Machado; Felipe Dilelis de Resende Sousa; Gerusa da Silva Salles Corrêa (Ciência e Agrotecnologia)
ABSTRACT Determining the actual lysine requirement is crucial as it is an essential amino acid and plays animportant role in the metabolism of broilers. In addition, it is the second limiting amino acid for broilers fed with rations formulated basedon corn and soybean meal. The aim of this study was to determine the digestible lysine requirement for male broilers with lower genetic potential for growth in a semi-confined system as well as to evaluate the effects of different values of digestible lysine on performance and carcass characteristics. A total of 300 broiler chickensfrom a commercial lineage EMBRAPA 041 were used with an average initial weight of 987 g. The broilers were distributed into 20 experimental units in a completely randomized design with five treatments (0.586; 0.746; 0.906; 1.066, and 1.226% digestible lysine), four replicates and 15 broilers per experimental unit.In both periods, there were linear effect of digestible lysine values on the lysine intake and lysine utilization efficiency and quadratic effect on final body weight, weight gain and feed: gain ratio.There was a quadratic effect on the absolute weight of carcasses, breast, thigh + drumstick and income gizzard.For rearing of male broilers with lesser genetic growth potential reared in semi-confinement, rations with 1.040% and 1.103% digestible lysine can be recommended for maximum weight gain in periods from 35 to 70 and 35 to 84 days of age, respectively.